Theoretical investigation of the enzymatic phosphoryl transfer of β-phosphoglucomutase: revisiting both steps of the catalytic cycle - Elsässer, Brigitta; Dohmeier-Fischer, Silvia; Fels, Gregor (Journal of Molecular Modeling)

Ultrasound-assisted catalytic synthesis of acyclic imides in the presence of p-toluenesulfonic acid under solvent free conditions - Nasr-Esfahani, Masoud; Montazerozohori, Morteza; Filvan Torkaman, Najmeh (Journal of the Serbian Chemical Society)
A rapid and convenient preparation of acyclic imides by the reaction of aliphatic and aromatic nitriles with acyclic carboxylic anhydride in the presence of catalytic amounts of p-toluenesulfonic acid under thermal or ultrasonic conditions is reported. The advantages of this procedure are moderate reaction times, good to excellent yields, use of inexpensive and ecofriendly catalyst. The reaction of nitriles with aliphatic anhydrides proceeds in thermal conditions, while by the use of ultrasound irradiations these reactions get accelerated.
Keywords: General Chemistry

Phosphonium Salt Catalyzed Addition of Diethylzinc to Aldehydes - Werner, Thomas; Riahi, Abdol; Schramm, Heiko (Synthesis)
Keywords: Organic Chemistry; Catalysis

Sodium Hydride Catalyzed Tishchenko Reaction - Werner, Thomas; Koch, Juliane (European Journal of Organic Chemistry)
Keywords: Organic Chemistry; Physical and Theoretical Chemistry

Phosphonium Salt Organocatalysis - Werner, Thomas (Advanced Synthesis & Catalysis)
Keywords: General Chemistry

Biomimetic Synthesis of Resorcylate Natural Products Utilizing Late Stage Aromatization: Concise Total Syntheses of the Marine Antifungal Agents 15G256ι and 15G256β - Navarro, Ismael; Basset, Jean-François; Hebbe, Séverine; Major, Sarah M.; Werner, Thomas; Howsham, Catherine; Bräckow, Jan; Barrett, Anthony G. M. (Journal of the American Chemical Society)
Keywords: Colloid and Surface Chemistry; Biochemistry; General Chemistry; Catalysis

Mesoporous CeO2: Synthesis by nanocasting, characterisation and catalytic properties - Roggenbuck, Jan; Schäfer, Hanno; Tsoncheva, Tanya; Minchev, Christo; Hanss, Jan; Tiemann, Michael (Microporous and Mesoporous Materials)
Mesoporous CeO2 was synthesised by using CMK-3 carbon as a structure matrix. Nitrogen physisorption, powder X-ray diffraction, transmission electron microscopy (TEM), selected-area electron diffraction (SAED), energy-dispersive X-ray (EDX), X-ray absorption near-edge structure (XANES), and thermal (TG/MS) analysis were used for their characterisation. Methanol decomposition to hydrogen, CO, and methane was used as a catalytic test reaction. The obtained products exhibit uniform pores with a diameter of ca. 5 nm in a two-dimensional hexagonal periodic arrangement, as well as interparticle porosity, broadly distributed around ca. 35 nm; the specific surface area is 148 m2 g−1. The pore walls are polycrystalline. The polycrystalline nature and high surface-to-volume ratio of the products is reflected in an increased signal intensity in X-ray absorption spectroscopy. The synthesis of CeO2 from Ce(NO3)3 within the pores of the carbon matrix and the subsequent thermal combustion of the carbon is monitored by thermal analysis. Catalytic tests reveal that the activity of the mesoporous products in methanol decomposition are substantially higher than for a non-porous sample.

Cerium-Catalyzed α-Hydroxylation Reactions of α-Cyclopropyl β-Dicarbonyl Compounds with Molecular Oxygen - Christoffers, Jens; Kauf, Thomas; Werner, Thomas; Rössle, Michael (European Journal of Organic Chemistry)
Keywords: Organic Chemistry; Physical and Theoretical Chemistry

Simple Method for the Preparation of Esters from Grignard Reagents and Alkyl 1-Imidazolecarboxylates - Werner, Thomas; Barrett, Anthony G. M. (The Journal of Organic Chemistry)
Keywords: Organic Chemistry

Cerium-catalyzed oxidative C–C bond forming reactions - Christoffers, Jens; Werner, Thomas; Rössle, Michael (Catalysis Today)
Keywords: General Chemistry; Catalysis

Cerium-Catalyzed, Aerobic Oxidative Synthesis of 1,2-Dioxane Derivatives from Styrene and Their Fragmentation into 1,4-Dicarbonyl Compounds - Rössle, Michael; Werner, Thomas; Frey, Wolfgang; Christoffers, Jens (European Journal of Organic Chemistry)
Keywords: Organic Chemistry; Physical and Theoretical Chemistry

Preparation of Acyloins by Cerium-Catalyzed, Direct Hydroxylation of β-Dicarbonyl Compounds with Molecular Oxygen - Christoffers, Jens; Werner, Thomas; Unger, Sven; Frey, Wolfgang (European Journal of Organic Chemistry)
Keywords: Organic Chemistry; Physical and Theoretical Chemistry

Formation of 1,4-Diketones by Aerobic Oxidative CC Coupling of Styrene with 1,3-Dicarbonyl Compounds - Rössle, Michael; Werner, Thomas; Baro, Angelika; Frey, Wolfgang; Christoffers, Jens (Angewandte Chemie International Edition)
Keywords: General Chemistry; Catalysis

Synthesis of a tin-functionalized cyclopentadiene derivative - Christoffers, Jens; Werner, Thomas; Baro, Angelika; Fischer, Peter (Journal of Organometallic Chemistry)
Keywords: Materials Chemistry; Inorganic Chemistry; Organic Chemistry; Physical and Theoretical Chemistry; Biochemistry

Straightforward Synthesis of (R)-(−)-Kjellmanianone - Christoffers, Jens; Werner, Thomas; Frey, Wolfgang; Baro, Angelika (Chemistry - A European Journal)
Keywords: General Chemistry; Catalysis; Organic Chemistry

α-Hydroxylation ofβ-Dicarbonyl Compounds - Christoffers, Jens; Baro, Angelika; Werner, Thomas (Advanced Synthesis and Catalysis)
Keywords: General Chemistry

Cerium-Catalyzed Reaction ofβ-Dicarbonyl Compounds with Styrene and Atmospheric Oxygen - Christoffers, Jens; Werner, Thomas; Frey, Wolfgang; Baro, Angelika (European Journal of Organic Chemistry)
Keywords: Organic Chemistry; Physical and Theoretical Chemistry

Construction of Quaternary Stereocenters by Nickel-Catalysis of Asymmetric Michael Reactions - Christoffers, Jens; Rößler, Ulrich; Werner, Thomas (European Journal of Organic Chemistry)
Keywords: Organic Chemistry; Physical and Theoretical Chemistry

Cerium-catalyzed α-Oxidation of β-Dicarbonyl Compounds with Molecular Oxygen - Christoffers, Jens; Werner, Thomas (Synlett)
Keywords: Organic Chemistry

A New Role of the Surfactant in the Synthesis of Mesostructured Phases: Dodecyl Phosphate as Template and Reactant for Aluminophosphates - Fröba, Michael; Tiemann, Michael (Chemistry of Materials)
Lamellar mesostructured aluminophosphates were synthesized from aluminum triisopropoxide and phosphoric acid; monododecyl phosphate surfactant was used as structure-directing template. Depending on the relative Al/P ratio in the samples, variable relative amounts of tetrahedrally and octahedrally coordinated Al are found, indicating that both aluminophosphate and aluminum oxide species (as thermodynamically favored) are being formed in the syntheses. This is investigated quantitatively by Al K-edge XANES spectroscopy. The same syntheses were carried out without phosphoric acid, resulting in similar lamellar structures. The inorganic lamellae of these products consist to a significant extent of aluminophosphate rather than exclusively of aluminum oxide, which means that the phosphate headgroups of the surfactant molecules become incorporated into the inorganic network. Thus, for the first time, the surfactant serves as both template and reactant.